(untitled) (International Seven Journal of Multidisciplinary, 2023)
The study sought to position the economic viability of energy generation through wind turbines. Wind turbines are used to convert part of the kinetic energy of winds into electrical energy, therefore, they are useful for knowing what the upper limit of extractable energy is, which requires them to be placed in an ideal situation in which processes are carried out in search of of maximum perfection. As seen, opportunities to significantly increase the supply of wind energy through the use of wind turbines already exist, but they are already sufficient to raise a series of points where it would be necessary to invest in the acquisition of knowledge and technological development. The Study was developed through a literature review.